Knowledge, Attitudes and Barriers Toward Medical Research Among Al-Neelain Medical Students, Sudan - Magid Omer Mahmoud Abdalla; Abdallah Ali Mohammed Salih; Obai Mohamed Ibrahim Suareldahab; Duaa Eihab Mohammedelfatih Abdulraheem; Duaa Abdelmonem Ahmed Elbasheer; Esraa Abdulbagi Hassan Abdallahbai (International Journal of Medical Students)
BACKGROUND: Early involvement of medical students in research during school years has led to excellence in the research field and clinical practice during their careers. Previous studies try to evaluate knowledge and attitudes toward medical research in medical students in many countries. Limited studies are conducted in Sudan. In This study, we aimed to assess knowledge to, and attitudes towards and identify barriers to medical research among medical students at Al-neelain University.